An exploration of the influence of Femvertising on brand resonance - Erasmus, Mikayla (The IIE, 2018)
This research paper explores Femvertising within a South African context. It is an exploration of how female South African consumers perceive Femvertising and the potential effects of Femvertising on brand resonance. This study further investigates the potential of Femvertising as a means of social change as well as the viability of the tactic used by Audi in its Femvertising advertisement. Femvertising can be defined as advertising that employs pro-female messages imagery and talent (SheKnows, 2016). The development of femvertising is a response to the exploitation and negative stereotyping that has for long been part of the advertising industry (Navarro & Llaguno, 2012). Many view femvertising as not only a positive change in how brands advertise, but also a potential vehicle for bringing about positive social change in terms of gender equality (SheKnows, 2016). Some however are not convinced and believe that Femvertising is merely a new form of exploiting the gender issues that women face in order to make a profit (Iqbal, 2015). The primary research question addressed in this explorative qualitative study was: How, if at all, does femvertising influence the brand resonance of female South African consumers? The sample of this study consisted of female South Africans between the ages of 25 and 35 who drive an Audi, or similar car, and are exposed to advertising. The qualitative data was collected via a focus group consisting of seven participants. One of the most significant findings of the study included that consumers view Femvertising as having a positive influence on brand resonates. It was evident that consumers resonate not only to Femvertising, but social messages in advertising as it curates an emotional and psychological connection to the brand, where consumers can relate to the brand more if they can identify themselves, or aspects of themselves in the brand messaging.
Keywords: Brand; Consumer behaviour; Advertising; Femvertising; Gender; Brand resonance